2022
DOI: 10.1042/bsr20212510
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNAs in stem cells: from basic research to clinical implications

Abstract: Circular RNAs (circRNAs) are a special class of endogenous RNAs with a wide variety of pathophysiological functions via diverse mechanisms, including transcription, miRNA sponge, protein sponge/decoy, and translation. Stem cells are pluripotent cells with unique properties of self-renewal and differentiation. Dysregulated circRNAs identified in various stem cell types can affect stem cell self-renewal and differentiation potential by manipulating stemness. However, the emerging roles of circRNAs in stem cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 184 publications
(182 reference statements)
0
3
0
Order By: Relevance
“…miRNAs could affect the differentiation and self-renewal potential of SCs by manipulating stemness [ 23 ]. KLF4 is a transcription factor highly conserved in evolution, of which modulation could significantly affect cell stemness [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs could affect the differentiation and self-renewal potential of SCs by manipulating stemness [ 23 ]. KLF4 is a transcription factor highly conserved in evolution, of which modulation could significantly affect cell stemness [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…CircZKSCAN1 blocks FMRP binding to CCAR1 mRNA and negatively modulates CSCs [ 136 ]. Certainly, research on circRNAs in CSCs is still in the initial stage [ 137 ]. However, it is believed that circRNA is a dazzling star in the diagnosis and treatment of cancer.…”
Section: Roles Of Circrnas In Stem Cellsmentioning
confidence: 99%
“…CircRNAs can affect the CSC phenotype via certain classical signaling pathways, including the Wnt/β-catenin signaling pathway [13], HIF1AN/Notch signaling pathway [14], JAK2/ STAT3 signaling pathway [15], and Hedgehog signaling pathway [16]. Other studies indicated that circRNAs may attenuate the therapeutic resistance of CSCs or act as potential vaccines in CSCtargeted therapies [17,18]. Therefore, further exploration into the functional role of circRNAs in CSCs may lead to new directions in cancer treatment.…”
Section: Introductionmentioning
confidence: 99%